Dampak Keberadaan Rumah Ulin Arya Sebagai Daya Tarik Wisata Terhadap Peningkatan Sosial Ekonomi (Studi Pada Masyarakat Bayur Kelurahan Sempaja Utara Samarinda) - Kasmita; Fareis Althalets (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the impact of the existence of Rumah Ulin Arya, a nature-based tourist destination, on the socio-economic improvement of the surrounding community. The type of research used in the research is qualitative, data is obtained through data collection methods, namely observation, interviews, and direct documentation in the tourist environment of Rumah Ulin Arya. The informants in this study are the head of the local RT, tourism managers, and local communities. The results of the study show that the existence of Rumah Ulin Arya has an impact on the community, especially a positive impact on socio-economic improvement. The impact of social improvement is to increase the insight of visitors and the community related to Indonesian culture by holding traditional events, empowering local communities by including the community in certain events, and increasing population mobility by encouraging development development. Meanwhile, the impact of economic improvement is the opening of new jobs and people's income so that it can improve people's living standards to improve people's skills in business innovation. As well as increasing regional revenue, namely by contributing to PAD (Regional Original Revenue) through tax payments such as entertainment taxes and restaurant taxes which are carried out transparently and on time.